Digital Activism and Collective Identity: “No Viral No Action” as Connective Action among Youth on Jakarta’s Air Pollution Issue - Yazied Taqiyuddin Ahmad; Lugina Setyawati (Jurnal Pendidikan Ilmu Sosial, 2024)
This study examines the role of digital activism in forming collective identity among youth through the “No Viral No Action” campaign, which addresses air pollution in Jakarta. Using a qualitative approach with netnography methods, data was collected via in-depth interviews and social media content analysis on X (Twitter) and Instagram. The study explores how Jakarta’s youth use digital platforms to organize social movements and raise environmental awareness. The findings reveal that digital activism fosters collective identity through inclusive and interactive participation. The “No Viral No Action” campaign successfully garnered widespread support with engaging communication strategies tailored to the younger generation. Participation in this campaign not only strengthened solidarity but also heightened awareness of the importance of collective action against air pollution. The campaign’s effectiveness is attributed to self-organizing networks and actions facilitated by various entities, including ordinary citizens, communities, and media. The study concludes that the connective action seen in this campaign highlights the significant potential of social media in driving social change. It also underscores the crucial role of digital technology in enabling active youth participation in environmental issues, impacting the dynamics of contemporary social movements.